2015
DOI: 10.1097/sla.0000000000000884
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of the Incidence of Pancreatic and Extrapancreatic Malignancies During Surveillance of Patients With Branch-duct Intraductal Papillary Mucinous Neoplasm

Abstract: BD-IPMN patients are at risk of pancreatic carcinogenesis. Although the 5-year incidence rate was as low as 1.4%, the surveillance protocol based on the current guidelines failed to identify a small subset of patients who progressed to advanced disease. Patients with BD-IPMN are not at risk of extrapancreatic carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 36 publications
(41 reference statements)
2
53
0
1
Order By: Relevance
“…Despite the fact that this is the first time that the problematic issue of when to stop surveillance of low-risk lesions was addressed, the poor evidence that is currently available limits its generalizability. Moreover, current literature shows contradictory results regarding this matter, with several studies that analyzed BD-IPMNs reporting the development of malignancy after the initial five year period (28,29,96) whereas other publications showed a trend towards stability once the initial surveillance period has passed (97,98). A recent study involving several institutions analyzed 310 patients with asymptomatic PCLs (99).…”
Section: Current Guidelines and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that this is the first time that the problematic issue of when to stop surveillance of low-risk lesions was addressed, the poor evidence that is currently available limits its generalizability. Moreover, current literature shows contradictory results regarding this matter, with several studies that analyzed BD-IPMNs reporting the development of malignancy after the initial five year period (28,29,96) whereas other publications showed a trend towards stability once the initial surveillance period has passed (97,98). A recent study involving several institutions analyzed 310 patients with asymptomatic PCLs (99).…”
Section: Current Guidelines and Recommendationsmentioning
confidence: 99%
“…Initially, the main recommendation was to resect them due to their malignant potential. However, several recent studies have reported significantly lower rates of malignant transformation (ranging from 2-6%) (26)(27)(28)(29), which has leaned the balance towards a more conservative approach.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective series reported distinct pancreatic adenocarcinoma in a different segment of the pancreas away from index IPMN lesion in up to 13 11% of patients during follow-up. [25][26][27][28][29][30][31] We observed 1 patient without WF with cyst size increasing by 50% during surveillance (with benign EUS-FNA cytology) who presented with pancreatic adenocarcinoma in a different part of the pancreas with liver metastasis after 22 months. These results highlight the "fielddefect concept" and the need for continued imaging surveillance in BD-IPMN.…”
Section: 24mentioning
confidence: 99%
“…In a recent series of 90 consecutive resected MCNs of the pancreas, only 4.4% were associated with invasive carcinoma [9] . The risk of progression to cancer is shown to be only 1.4% following 5 years' surveillance of non-resected BD-IPMN [10] .…”
Section: Editorialmentioning
confidence: 99%
“…IPMNs involving only the branch ducts are difficult to handle. The risk for cancer is lower than for main-duct or mixed type IPMN, and according to large studies the incidence of cancer during follow-up seems to be very low [10] . If there are multiple lesions, the diagnosis of IPMN is likely, and the current guidelines for the management of these patients seem to be safe.…”
Section: Editorialmentioning
confidence: 99%